Personal resources and daily life fatigue in caregivers of persons with paraplegia - Woźniewicz, Agnieszka; Kalinowska, Joanna; Basińska, Małgorzata Anna; Pietrulewicz, Bogdan (Department of Psychology, University of Wrocław, 2014)
Taking care of a paraplegic may contribute to the caregiver’s fatigue. Sixty family caregivers participated in our study, out of which 30 provided care for paraplegics in hospital, and 30 for paraplegics at home. The Orientation to Life Qestionnaire (SOC-29) was used to measure individual sense of coherence, The Life Orientation Test – Revised for dispositional optimism, The Polish Resiliency Assessment Scale for resiliency, and The Daily Life Fatigue Questionnaire for daily life fatigue. In order to collect data about caregivers an individual examination was applied. People with higher personal resource levels such as sense of coherence, optimism and resiliency are characterized by less severe daily life fatigue.
Keywords: daily life fatigue; paraplegia; personal resources; caregiver